2021
DOI: 10.1126/sciadv.abj9247
|View full text |Cite
|
Sign up to set email alerts
|

FOXN1 forms higher-order nuclear condensates displaced by mutations causing immunodeficiency

Abstract: A dominant transcription factor mutation disrupting nuclear liquid phase separation causes human immunodeficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…STMN2 encodes a microtubule stability regulator, which can regulate the assembly and decomposition of tubulin, stabilize microtubules, and thus control the lengths of the neurites in cortical neurons [ 41 ]. FOXN1 is a transcription regulator that regulates the development differentiation and function of thymic epithelial cells in the thymus [ 42 ]. FOXN1 mutation-mediated immune deficiency is typically associated with severe combined immunodeficiency [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…STMN2 encodes a microtubule stability regulator, which can regulate the assembly and decomposition of tubulin, stabilize microtubules, and thus control the lengths of the neurites in cortical neurons [ 41 ]. FOXN1 is a transcription regulator that regulates the development differentiation and function of thymic epithelial cells in the thymus [ 42 ]. FOXN1 mutation-mediated immune deficiency is typically associated with severe combined immunodeficiency [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To probe the utility of the new set of cell surface markers to phenotype altered TEC scaffolds, we next analysed the composition of the thymic epithelia in FOXN1 Δ505/WT mice which express a dominant negative mutation of FOXN1 and consequently show substantial defects in TEC differentiation (Rota et al, 2021). A previous scRNAseq-based analysis of these animals revealed a relative enrichment of perinatal and mature cTEC against a reduction of tuft-like mTEC whereas the frequency of intertypical TEC remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Mice heterozygous for a Foxn1 allele with a single nucleotide loss at position 1470 (designated FOXN1 Δ505/WT ) were generated at the Genome Engineering Facility of the MRC Weatherall Institute of Molecular Medicine, University of Oxford as previously described (Rota et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Devoted functional studies elucidated the mechanism by which this and other C-terminal mutants exert a dominant-negative effect on wild-type FOXN1. 191 The broad spectrum of mechanism by which monoallelic FOXN1 variants lead to different degrees of thymic hypoplasia has been recently studied by Moses et al in 35 selected FOXN1 variants that were tested with transcriptional reporter assays, imaging studies, and reaggregate thymus organ cultures. This approach allowed to categorize the variants into benign, loss-or gain-of-function, and/or dominant-negatives.…”
Section: Consequences Of Thymic Hypofunctionmentioning
confidence: 99%
“…Finally a recent study identified three individuals with the same FOXN1 c.1370delA frameshift mutation. Devoted functional studies elucidated the mechanism by which this and other C‐terminal mutants exert a dominant‐negative effect on wild‐type FOXN1 191 . The broad spectrum of mechanism by which monoallelic FOXN1 variants lead to different degrees of thymic hypoplasia has been recently studied by Moses et al.…”
Section: Primary Thymic Defectsmentioning
confidence: 99%